Research method in applied linguistics : quantitative, qualitative, and mixed methodologies - Dornyei, Zoltan (Oxford applied linguistics, 2007)
Practical, hands-on focus. Accessible style, even when discussing statistical methods. Integrated coverage of both qualitative and quantitative research. Pioneering discussion of mixed methods research in applied linguistics. Examples of how to report research results